Partial regularity for non-autonomous degenerate quasi-convex functionals with general growth. (May 2020) - Celada, Pietro; Ok, Jihoon
Abstract: We study partial C 1, α  – regularity of minimizers of quasi-convex variational integrals with non-standard growth. We assume in particular that the relevant integrands satisfy an Orlicz's type growth condition, i.e. a so-called general growth condition. Moreover, the functionals are supposed to be non-autonomous and possibly degenerate.